Ti-reinforced magnesium-based composite material and preparation method and application thereof
By preparing Ti reinforced magnesium-based composite materials, a porous Ti frame was made by sintering and ultrasonic treatment processes, and immersing it in magnesium-aluminum-zinc melt, solving the problem of insufficient strength and plasticity of magnesium-based composite materials, and achieving high mechanical properties and low density material preparation.
Patent Information
- Application Number
- CN202410958501.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-07-17
AI Technical Summary
Magnesium-based composites have limited their wide application in aerospace, engineering and construction fields due to their poor strength and plasticity.
By preparing Ti-reinforced magnesium-based composite materials, the components of 35-45% titanium, 5-8% aluminum, 0.5-2% zinc, and 49.5-55% magnesium were prepared, and the porous Ti frame was made by sintering and ultrasonic treatment, and the composite material was made by immersing it in the magnesium aluminum-zinc melt.
Ti-reinforced magnesium-based composite materials with low density, light weight and high mechanical properties have been achieved, which are manifested as significantly improved in yield strength, tensile strength, elongation, elastic modulus and compressive strength, which are better than materials produced in existing processes.
Smart Images

Figure BDA0004949596110000091 
Figure HDA0004949596130000011 
Figure HDA0004949596130000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials, and in particular relates to a Ti-reinforced magnesium-based composite material and a preparation method and application thereof. Background Art
[0002] Magnesium-based composites are one of the lightest metal structural materials currently used in engineering applications. With its advantages of light weight, high specific strength and specific stiffness, magnesium-based composites have rapidly become the most promising lightweight structural materials after steel and aluminum alloys. Due to its low density, excellent comprehensive mechanical properties, and abundant reserves, magnesium has attracted extensive attention in many fields such as automobiles, aerospace, and 3C. However, its poor strength and plasticity have hindered its widespread application in many fields. Summary of the invention
[0003] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a Ti-reinforced magnesium-based composite material.
[0004] A second object of the present invention is to provide a method for preparing a Ti-reinforced magnesium-based composite material.
[0005] A third object of the present invention is to provide application of the above-mentioned Ti-reinforced magnesium-based composite material and / or the Ti-reinforced magnesium-based composite material obtained by the above-mentioned preparation method in aerospace materials, engineering materials or building materials.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a Ti-reinforced magnesium-based composite material, comprising the following components in mass percentage: 35-45% titanium, 5-8% aluminum, 0.5-2% zinc, and 49.5-55% magnesium.
[0008] Preferably, the Ti-reinforced magnesium-based composite material further comprises trace elements with a mass percentage of 0 to 0.005%, and the mass percentage of the trace elements is not 0%; the trace elements are selected from at least one of Cu, Fe, Mn, Ni and Si.
[0009] Preferably, the titanium is distributed in the Ti-reinforced magnesium-based composite material in the form of a three-dimensional network.
[0010] The second aspect of the present invention provides a method for preparing the Ti-reinforced magnesium-based composite material according to the first aspect of the present invention, comprising the following steps:
[0011] S1: pressing titanium powder into a shape, and then sintering at 1550-1600°C to obtain a porous Ti framework;
[0012] S2: Under a protective atmosphere, the porous Ti framework is immersed in a magnesium-aluminum-zinc melt at a moving speed of 0.1 to 0.3 m / min and subjected to ultrasonic treatment, and the Ti-reinforced magnesium-based composite material is obtained after cooling. If the immersion moving speed is too slow, the magnesium-aluminum-zinc melt will oxidize and burn, which is dangerous. If the immersion moving speed is too fast, the gas in the porous Ti framework cannot be discharged, forming closed pores and reducing density.
[0013] The present invention adopts sintering at 1550-1600°C, and the sintering temperature is close to the melting point temperature, which can maximize the mechanical properties of the porous Ti framework itself while protecting the porosity, thereby improving the performance of the composite material. The sintering process is completed in one time, which not only shortens the preparation process and time cost, but also reduces the risk of Ti oxidation during secondary or multiple sintering processes. In addition, when the porous Ti framework is immersed in the magnesium-aluminum-zinc melt, the present invention adopts an ultrasonic treatment process, the purpose of which is to eliminate the bubbles inside the porous Ti framework after immersion, improve the bonding effect between the porous Ti framework and the magnesium matrix, and thus improve the performance of the composite material.
[0014] Preferably, the protective atmosphere is CO with a volume ratio of (3-6):1 2 and F 6 Mixture of S. CO 2 and F 6 The S mixed gas has the function of isolating oxygen and capturing oxygen at the same time, thereby protecting the magnesium-aluminum-zinc melt, preventing oxidation combustion, and improving safety. In addition, it improves the purity of the magnesium-aluminum-zinc melt, reduces oxide pollution, and increases the mechanical properties of the composite material.
[0015] Preferably, the ultrasonic treatment time is 5 to 10 minutes.
[0016] Preferably, the ultrasonic treatment frequency is 50-100 Hz.
[0017] Preferably, the sintering time is 1.5 to 3 hours.
[0018] Preferably, the temperature of the magnesium-aluminum-zinc melt is 720-750°C.
[0019] Preferably, the titanium powder is a powder treated by soaking in a citric acid solution; further preferably, the titanium powder is a powder treated by soaking in a citric acid solution and then washed and dried.
[0020] Preferably, in the citric acid solution, the mass percentage of citric acid is 5-20%.
[0021] Preferably, the soaking treatment time is 10 to 30 minutes. Soaking titanium powder in citric acid solution can remove impurity elements on the surface of titanium powder, avoid introducing too many impurities into the Ti-reinforced magnesium-based composite material, and thus affect the mechanical properties of the composite material. In addition, removing impurity elements on the surface of titanium powder can also enhance the bonding strength between the porous Ti framework and the magnesium matrix, making the two closely bonded, and further improving the mechanical properties of the composite material.
[0022] Preferably, the particle size of the titanium powder is 400-600 μm.
[0023] Preferably, the titanium powder is an irregularly shaped powder. The use of irregular large-size titanium powder is to allow the prepared porous Ti framework to have pores of various pore sizes, thereby improving the bonding strength between the porous Ti framework and the magnesium matrix.
[0024] Preferably, the pressure in the pressing step is 30 to 50T (T is tons), and the pressing time is 3 to 10 minutes.
[0025] Preferably, the pressure increasing rate in the compression molding step is 0.05 to 0.3 T / s.
[0026] Preferably, the sintering step is performed in a high vacuum sintering furnace.
[0027] Preferably, the sintering step is specifically: evacuating to a vacuum degree of ≤2*10 -3 MPa, then fill with nitrogen to normal pressure, and then evacuate to a vacuum degree of ≤2*10 -3 MPa, stop, repeat this step 1 to 3 times, heat to 1550-1600℃, sinter for 1.5-3h, and cool.
[0028] Preferably, the preparation method of the magnesium-aluminum-zinc melt is: under a protective atmosphere, adding magnesium-aluminum-zinc raw materials into a container, heating to 680-700°C and mixing, removing impurities on the surface of the melt; and then heating to 720-750°C to obtain the aluminum-magnesium-zinc melt.
[0029] Preferably, the CO 2 and F 6 The flow rate of the mixed gas of S is 0.3-1 nL / min; further preferably, in the step of adding the magnesium-aluminum-zinc raw material into the container, CO 2 and F 6 The flow rate of the mixed gas of S is 0.3-0.8 nL / min; when the temperature is raised to 720-750°C, CO 2 and F 6 The flow rate of the S mixed gas is 0.5 to 1 nL / min.
[0030] Preferably, the mixing is carried out by stirring. The purpose of the stirring process is to accelerate the formation of the alloy and remove the bubbles in the melt to achieve a homogenization effect.
[0031] Preferably, the stirring time is 15 to 35 minutes.
[0032] Preferably, the stirring speed is 60-100 r / min.
[0033] Preferably, the cooling step in step S2 is: after cooling to 550-580° C., immersing in dry sand and cooling to room temperature to obtain the product.
[0034] The third aspect of the present invention provides the use of the Ti-reinforced magnesium-based composite material described in the first aspect of the present invention and / or the Ti-reinforced magnesium-based composite material prepared by the preparation method described in the second aspect of the present invention in aerospace materials, engineering materials or building materials.
[0035] The beneficial effects of the present invention are as follows: the Ti-reinforced magnesium-based composite material of the present invention has low density, light weight and high mechanical properties, specifically: yield strength of 457-489 MPa, tensile strength of 503-512 MPa, elongation of 5.5-5.8%, elastic modulus of 65.28-69.85 GPa, and compressive strength of 451-478 MPa, which is significantly better than the Ti-reinforced magnesium-based composite material obtained by the existing process.
[0036] The preparation method of the Ti-reinforced magnesium-based composite material in the present invention can obtain a porous Ti frame through press molding and sintering steps, and the porous Ti frame is immersed in a magnesium-aluminum-zinc melt, and the magnesium-aluminum-zinc melt is immersed in the porous Ti frame, so as to obtain a Ti-reinforced magnesium-based composite material with excellent mechanical properties. The preparation method is simple, has few steps, is easy to operate, has low cost and high production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the metallographic microstructure OM image of the Ti-reinforced magnesium-based composite material in Example 1.
[0038] Figure 2 This is the SEM image of the Ti-reinforced magnesium-based composite material in Example 1.
[0039] Figure 3 This is a local SEM enlarged image of the Ti-reinforced magnesium-based composite material in Example 1.
[0040] Figure 4 This is a local SEM enlarged image of the Ti-reinforced magnesium-based composite material in Example 1.
[0041] Figure 51 and 2 are scanning electron microscope images of the Ti-reinforced magnesium-based composite materials in Example 1 and Comparative Example 1.
[0042] Figure 6 This is a stress-strain curve test diagram of the Ti-reinforced magnesium-based composite material in Example 1.
[0043] Figure 7 It is a stress-strain curve test diagram of the Ti-reinforced magnesium-based composite material in Examples 1 to 3.
[0044] Figure 8 1 is a stress-strain curve test diagram of the Ti-reinforced magnesium-based composite material in Example 1 and Comparative Example 1.
[0045] Fig. 9 It is a stress-strain curve test diagram of the Ti-reinforced magnesium-based composite material in Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0046] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0047] The information of the materials used in the examples and comparative examples of the present invention are as follows:
[0048] Ti powder: purity ≥99.99%, particle size 500±100μm;
[0049] Pure aluminum ingot: purity ≥99.95%;
[0050] Pure zinc ingot: purity ≥99.95%;
[0051] Pure magnesium ingot: purity ≥99.95%.
[0052] Example 1
[0053] This example provides a Ti-reinforced magnesium-based composite material, the components of which are shown in Table 1 below.
[0054] Table 1 Composition of Ti-reinforced magnesium-based composite materials (mass percentage / %)
[0055] element Ti Al Zn Mg (Cu,Fe,Mn,Ni,Si) content 44% 5% 0.9% 50% margin
[0056] The Ti-reinforced magnesium-based composite material in this example is prepared by the following preparation method, and the specific steps are as follows:
[0057] (1) Prepare the raw materials according to the raw material preparation formula recorded in Table 2;
[0058] Table 2 Preparation of raw material formula for Ti-reinforced magnesium-based composite materials (mass percentage / %)
[0059] Ti(%) Al(%) Zn(%) Mg(%) Ingredient Value 45 6 2 margin
[0060] (2) Surface treatment: The Ti powder was immersed in a 20% citric acid solution for 30 min to remove surface impurities, and then washed and dried.
[0061] (3) Pressing: The dried Ti powder was loaded into a square mold of 100 mm*100 mm*40 mm, and a vertical pressure of 30 T (T is tons) was applied to the mold at a pressure increase rate of 0.1 T / S. The pressure was maintained for 3 min. After demolding, a Ti block of 100 mm*100 mm*35 mm was obtained.
[0062] (4) Sintering: Place the pressed Ti block into a high vacuum sintering furnace and evacuate to a vacuum degree of 2*10 -3 MPa, stop evacuating, fill with argon to normal pressure, and evacuate again to 2*10 -3 MPa, repeat the above steps 3 times, then heat the high vacuum sintering furnace to 1550℃, keep it warm for 120min, and cool it to room temperature with the furnace to obtain the sintered Ti frame.
[0063] (5) Preheat the crucible: Set the temperature of the electric melting furnace to 450°C.
[0064] (6) Charging the furnace: 6 wt% pure aluminum ingot (purity ≥ 99.95%), 2 wt% pure zinc ingot (purity ≥ 99.95%), and 47 wt% pure magnesium ingot (purity ≥ 99.95%) were successively added into the furnace, and CO was continuously introduced. 2 and F 6 S mixed gas, CO 2 and F 6 The ratio of the S mixed gas is 6:1 and the flow rate is 0.3nL / min.
[0065] (7) Preparation of melt: Heat the electric furnace to 700°C, remove the scum on the surface of the melt, and stir for 15 minutes at a stirring speed of 100 r / min. Remove the scum on the surface of the melt again. When the melt temperature rises to 750°C, stop heating and continue to introduce CO into the crucible. 2 and F 6 S mixed gas, CO 2 and F 6 The ratio of the S mixed gas is 6:1, and the flow rate is 0.5nL / min.
[0066] (8) Infiltration: The sintered Ti frame is slowly sunk into the magnesium alloy melt at a sinking rate of 0.3 m / min. After the Ti frame is slowly and completely sunk, it is vibrated by ultrasonic vibration for 10 min at a vibration frequency of 50 Hz. The crucible is taken out of the electric melting furnace and cooled in the air. When the melt temperature is cooled to 580°C, the infiltrated Ti block is taken out and buried in dry sand to cool to room temperature, washed, and dried to obtain the Ti-reinforced magnesium-based composite material in this example.
[0067] Example 2
[0068] This example provides a Ti-reinforced magnesium-based composite material, the components of which are shown in Table 3 below.
[0069] Table 3 Composition of Ti-reinforced magnesium-based composite materials (mass percentage / %)
[0070] element Ti Al Zn Mg (Cu,Fe,Mn,Ni,Si) content 41% 5.6% 1.3% 52% margin
[0071] The Ti-reinforced magnesium-based composite material in this example is prepared by the following preparation method, and the specific steps are as follows:
[0072] (1) Prepare the raw materials according to the raw material preparation formula recorded in Table 4;
[0073] Table 4 Preparation of raw material formula for Ti-reinforced magnesium-based composite materials (mass percentage / %)
[0074] Ti(%) Al(%) Zn(%) Mg(%) Ingredient Value 42 6 2 margin
[0075] (2) Surface treatment: The Ti powder was immersed in a 20% citric acid solution for 30 min to remove surface impurities, and then washed and dried.
[0076] (3) Pressing: The dried Ti was loaded into a square mold of 100 mm*100 mm*40 mm, and a vertical pressure of 30 T was applied to the mold, with a pressure increase rate of 0.1 T / S and a pressure holding time of 3 min. After demolding, a Ti block of 100 mm*100 mm*35 mm was obtained.
[0077] (4) Sintering: Place the pressed Ti block into a high vacuum sintering furnace and evacuate to a vacuum degree of 2*10 -3 MPa, stop evacuating, fill with argon to normal pressure, and evacuate again to 2*10 -3 MPa, repeat the above steps 3 times, heat to 1550℃, keep warm for 120min, cool to room temperature with the furnace, and obtain the sintered Ti frame.
[0078] (5) Preheat the crucible: Set the temperature of the electric melting furnace to 450°C.
[0079] (6) Charging the furnace: 6wt% pure aluminum ingot (purity ≥ 99.95%), 2wt% pure zinc ingot (purity ≥ 99.95%), and 50wt% pure magnesium ingot (purity ≥ 99.95%) were successively added into the furnace and CO was continuously introduced. 2 and F 6 S mixed gas, ratio is 6:1, flow rate is 0.3nL / min.
[0080] (7) Preparation of melt: Heat the alloy melt to 700°C, remove the scum on the melt surface, and stir for 15 minutes at a stirring speed of 100 r / min. Remove the scum on the melt surface again. When the melt temperature rises to 750°C, stop heating and continue to introduce CO into the crucible. 2 and F 6 S mixed gas, ratio is 6:1, flow rate is 0.5nL / min.
[0081] (8) Infiltration: The sintered Ti frame is slowly sunk into the magnesium alloy melt at a sinking rate of 0.3 m / min. After the Ti frame is slowly and completely sunk, it is vibrated by ultrasonic vibration for 10 min at a vibration frequency of 50 Hz. The crucible is taken out of the electric furnace and cooled in the air. When the melt temperature is cooled to 580°C, the infiltrated Ti frame is taken out and buried in dry sand to cool to room temperature, washed, and dried to obtain the Ti-reinforced magnesium-based composite material in this example.
[0082] Example 3
[0083] This example provides a Ti-reinforced magnesium-based composite material, the components of which are shown in Table 5 below.
[0084] Table 5 Composition of Ti-reinforced magnesium-based composite materials (mass percentage / %)
[0085] element Ti Al Zn Mg (Cu,Fe,Mn,Ni,Si) content 37% 6.9% 1.8% 54.2% margin
[0086] The Ti-reinforced magnesium-based composite material in this example is prepared by the following preparation method, and the specific steps are as follows:
[0087] (1) Prepare the raw materials according to the raw material preparation formula recorded in Table 6;
[0088] Table 6 Preparation of raw material formula for Ti-reinforced magnesium-based composite materials (mass percentage / %)
[0089] Ti(%) Al(%) Zn(%) Mg(%) Ingredient Value 38 9 3 margin
[0090] (2) Surface treatment: The Ti powder was immersed in a 20% citric acid solution for 30 min to remove surface impurities, and then washed and dried.
[0091] (3) Pressing: The dried Ti powder was loaded into a square mold of 100 mm*100 mm*40 mm, and a vertical pressure of 30 T was applied to the mold, with a pressure increase rate of 0.1 T / S and pressure maintained for 3 min. After demolding, a Ti block of 100 mm*100 mm*35 mm was obtained.
[0092] (4) Sintering: Place the pressed Ti block into a high vacuum sintering furnace and evacuate to a vacuum degree of 2*10 -3 MPa, stop evacuating, fill with argon to normal pressure, and evacuate again to 2*10 -3 MPa, repeat the above steps 3 times, heat to 1550℃, keep warm for 120min, cool to room temperature with the furnace, and obtain the sintered Ti frame.
[0093] (5) Preheat the crucible: Set the temperature of the electric melting furnace to 450°C.
[0094] (6) Charging the furnace: 9wt% pure aluminum ingot (purity ≥ 99.95%), 3wt% pure zinc ingot (purity ≥ 99.95%), and 50wt% pure magnesium ingot (purity ≥ 99.95%) were successively added into the furnace and CO was continuously introduced. 2 and F 6 S mixed gas, ratio is 6:1, flow rate is 0.3nL / min.
[0095] (7) Preparation of melt: Heat the alloy melt to 700°C, remove the scum on the melt surface, and stir for 15 minutes at a stirring speed of 100 r / min. Remove the scum on the melt surface again. When the melt temperature rises to 750°C, stop heating and continue to introduce CO into the crucible. 2 and F 6 S mixed gas, ratio is 6:1, flow rate is 0.5nL / min.
[0096] (8) Infiltration: The sintered Ti frame is slowly sunk into the magnesium alloy melt at a sinking rate of 0.3 m / min. After the Ti frame is slowly and completely sunk, it is vibrated by ultrasonic vibration for 10 min at a vibration frequency of 100 Hz. The crucible is taken out of the electric furnace and cooled in the air. When the melt temperature is cooled to 580°C, the infiltrated Ti frame is taken out and buried in dry sand to cool to room temperature. It is then washed and dried to obtain the Ti-reinforced magnesium-based composite material in this example.
[0097] Comparative Example 1
[0098] This example provides a method for preparing a Ti-reinforced magnesium-based composite material, and the specific steps are as follows:
[0099] (1) Cold pressing loose titanium powder for medium temperature pre-sintering: titanium powder is loaded into a mold, and a pressure of 12 MPa is applied to compact the titanium powder. The compacted titanium powder and the mold are placed in a vacuum sealed container for vacuum sintering. The sintering temperature is raised from room temperature to 1000°C, and then kept at 1000°C for 1.5 hours, and then cooled to room temperature to obtain a porous titanium pre-sintered body.
[0100] (2) Rough machining of porous titanium pre-sintered body: rough machining the porous titanium pre-sintered body into the shape and size required by the device blank by means of mechanical machining, leaving a size margin for the volume shrinkage of the porous titanium pre-sintered body and fine machining in the later stage, and obtaining the part to be sintered;
[0101] (3) High-temperature final sintering: the part to be sintered is placed in a clean, sealed container for vacuum high-temperature sintering at a sintering temperature of 1300°C for 3 hours to obtain a porous titanium preform;
[0102] (4) Magnesium alloy infiltration: The Mg-9Al-1Zn magnesium alloy is melted into magnesium alloy liquid under the protection of protective gas, and then kept at 80°C above the melting point of the magnesium alloy for 1 hour, and then infiltrated into a porous titanium preform, and air-cooled or water-cooled to room temperature to obtain the Ti-reinforced magnesium-based composite material in this example.
[0103] Comparative Example 2
[0104] This example provides a method for preparing a Ti-reinforced magnesium-based composite material, which is prepared by a stirring casting method, and the specific steps are as follows:
[0105] (1) Prepare the following raw materials according to the mass percentage of each raw material recorded in Table 7 below:
[0106] Table 7 Preparation of raw material formula for Ti-reinforced magnesium-based composite materials (mass percentage / %)
[0107] Ti(%) Al(%) Zn(%) Mg(%) Ingredient Value 45 6 2 margin
[0108] (2) Preheat the crucible: Set the temperature of the electric melting furnace to 450-580℃.
[0109] (3) Charging the furnace: 6wt% pure aluminum ingot (purity ≥ 99.95%), 2wt% pure zinc ingot (purity ≥ 99.95%), and 47wt% pure magnesium ingot (purity ≥ 99.95%) were added into the furnace in sequence, and CO was continuously introduced. 2 and F 6 S mixed gas, ratio is 6:1, flow rate is 0.3nL / min.
[0110] (4) Preparation of melt: The melt was heated to 700°C, the scum on the surface of the melt was removed, and the heating was stopped when the melt temperature reached 750°C, and CO was continuously introduced into the crucible.2 and F 6 S mixed gas, with a flow rate of 0.5 nL / min. (5) Stirring and mixing: Ti particles are slowly added to the AZ91 magnesium alloy melt and stirred continuously at a stirring rate of 60 r / min for 30 min. The crucible is taken out of the electric furnace and cooled in air to obtain the Ti-reinforced magnesium-based composite material in this example.
[0111] Performance Testing
[0112] (1) Surface morphology test
[0113] The metallographic microstructure OM image and scanning electron microscope SEM image of the Ti-reinforced magnesium-based composite material in Example 1 were tested respectively. The specific test results are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the Ti in the magnesium-based composite material in Example 1 is continuously and evenly distributed, forming a large number of multi-sized pores, which is conducive to the infiltration of the magnesium alloy melt and reduces the generation of closed pores. The composite material formed after the magnesium alloy penetrates into the Ti framework is dense and pore-free. In addition, the interconnection of multi-sized pores helps to disperse the stress during the load-bearing process, hinders the expansion of cracks, and helps to improve the mechanical properties of the magnesium-based composite material.
[0114] The local SEM magnified image of the Ti-reinforced magnesium-based composite material in Example 1 was tested using a high-power scanning electron microscope. Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 It can be seen that there is an irregular serrated connection at the interface between the Ti frame and the magnesium matrix, and the interface is tightly bonded without obvious pores and gaps. The tight interface bonding helps to hinder the nucleation of cracks, and the serrated structure increases the tensile resistance of the composite material, further illustrating that the Ti-reinforced magnesium-based composite material prepared in the present invention has a good structure.
[0115] The scanning electron microscope images of the magnesium-based composite materials in Test Example 1 and Comparative Example 1 are as follows: Figure 5 As shown, Figure 5 (a) and Figure 5 (b) are scanning electron microscope images of the magnesium-based composite materials of Example 1 and Comparative Example 1, respectively. Figure 5It can be seen that there are still a large number of dispersed spherical Ti particles in the Ti-reinforced magnesium-based composite material in Comparative Example 1, which means that the bonding of the Ti framework itself is poor and the strength is low. This phenomenon is caused by the low sintering temperature when preparing the Ti framework, which cannot achieve the melting and bonding of the selected spherical Ti powder, reducing the strength of the framework itself and resulting in poor mechanical properties of the composite material. In addition, the Ti framework in Comparative Example 1 is mostly spherical in surface, which is not conducive to bonding with the magnesium alloy matrix, resulting in the appearance of cracks during loading and reducing the mechanical properties of the composite material.
[0116] (2) Mechanical properties test
[0117] The Ti-reinforced magnesium-based composite material in Example 1 was subjected to a GB / T 228.1-2021 tensile test, and the obtained stress-strain curve is as follows: Figure 6 The tensile test data are shown in Table 8. Figure 6 It can be seen that the Ti-reinforced magnesium-based composite material in Example 1 has ultra-high mechanical properties, which are much higher than the current cast magnesium alloy materials. It has ultra-high tensile properties and also has a good elastic modulus. A better elastic modulus means that it is more suitable for future engineering application scenarios.
[0118] The Ti-reinforced magnesium-based composite materials in Examples 1 to 3 were subjected to tensile tests, and the obtained stress-strain curves are shown in FIG. Figure 7 The tensile test data are shown in Table 8. Figure 7 It can be seen that the mechanical properties of the Ti-reinforced magnesium-based composite materials in Examples 1 to 3 are related to the content of the Ti framework. As the Ti content increases, the mechanical properties of the magnesium-based composite materials also improve.
[0119] The Ti-reinforced magnesium-based composite materials in Example 1 and Comparative Example 1 were subjected to tensile tests, and the obtained stress-strain curves are shown in FIG. Figure 8 The tensile test data are shown in Table 8 below.
[0120] The Ti-reinforced magnesium-based composite materials in Example 1 and Comparative Example 2 were subjected to tensile tests, and the obtained stress-strain curves are shown in FIG. Fig. 9 The tensile test data are shown in Table 8 below.
[0121] Table 8 Tensile test results of Ti-reinforced magnesium-based composites
[0122]
[0123] It can be seen from Table 8 that compared with Comparative Examples 1 to 2, the performance of the magnesium-based composite materials in Examples 1 to 3 is significantly improved, specifically: the yield strength is 457 to 489 MPa, the tensile strength is 503 to 512 MPa, the elongation is 5.5 to 5.8%, the elastic modulus is 65.28 to 69.85 GPa, and the compressive strength is 451 to 478 MPa; the reason for the performance improvement may be that the Ti framework is evenly distributed in a mesh inside the magnesium-based composite material, and as a reinforcing phase, it bears the external force applied when the material is deformed, and the Ti framework is tightly combined with the magnesium-based composite matrix, which helps to conduct and carry stress during deformation.
[0124] Compared with Comparative Example 1, the reasons for the significant improvement in the strength and elastic modulus of Examples 1 to 3 may be: the different components of the composite material, the selection of Ti frame raw material powder, the surface deoxidation process of titanium powder, the improvement of the frame sintering process, the different protective atmospheres during the infiltration process, the adjustment of the formula and process such as ultrasonic vibration, which improves the compatibility between Ti and other components in the magnesium matrix, makes the combination of Ti and the magnesium matrix closer, and further improves its performance.
[0125] Compared with Comparative Example 2, the reason why the strength and elastic modulus of Examples 1 to 3 are significantly improved may be that the reinforcement method of Ti on the magnesium-based composite material in Comparative Example 2 is a dispersion reinforcement method, which cannot achieve uniform dispersion of the reinforcement Ti, resulting in poor strength of the composite material. However, the Ti inside the Ti-reinforced magnesium-based composite material prepared in Examples 1 to 3 is uniformly distributed in a network, and as a reinforcement phase, it bears the external force applied when the material is deformed, and the tight combination of the Ti framework and the matrix is conducive to the conduction and bearing of stress during deformation, thereby improving the mechanical properties of the composite material.
[0126] In summary, the present invention prepares a porous Ti framework through a vacuum solid-state sintering process. During the preparation process, pickling can effectively remove impurity elements on the surface of the Ti powder, which is beneficial to improving the mechanical properties of the magnesium-based composite material; selecting Ti powder with a particle size of 500±100μm and adopting a molding method can effectively improve the porosity and frame strength, which is beneficial to reducing the density of the magnesium-based composite material and improving the mechanical properties of the magnesium-based composite material. The infiltration process of the present invention is simple and efficient, and the prepared magnesium-based composite material does not need to undergo related heat treatment processes such as solid solution, aging, and annealing, which reduces the steps of product production and greatly saves costs. The tensile strength of the magnesium-based composite material prepared by this method reaches 500MPa.
[0127] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A Ti-reinforced magnesium-based composite material, characterized in that: It includes the following components in mass percentage: titanium 35-45%, aluminum 5-8%, zinc 0.5-2%, magnesium 49.5-55%; The Ti-reinforced magnesium-based composite material is prepared by a preparation method comprising the following steps: S1: Pressing titanium powder into a shape and then sintering at 1550-1600°C to obtain a porous Ti framework; S2: Under a protective atmosphere, immersing the porous Ti framework into a magnesium-aluminum-zinc melt at a moving rate of 0.1-0.3 m / min and ultrasonically treating the melt, and obtaining the Ti-reinforced magnesium-based composite material after cooling; The titanium is distributed in the Ti-reinforced magnesium-based composite material in a three-dimensional network shape.
2. The Ti-reinforced magnesium-based composite material according to claim 1, characterized in that: The Ti-reinforced magnesium-based composite material also includes trace elements with a mass percentage of 0-0.005%, and the mass percentage of the trace elements is not 0%; the trace elements are selected from at least one of Cu, Fe, Mn, Ni, and Si.
3. The method for preparing the Ti-reinforced magnesium-based composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: Pressing titanium powder into a shape and then sintering at 1550-1600°C to obtain a porous Ti framework; S2: Under a protective atmosphere, immersing the porous Ti framework into a magnesium-aluminum-zinc melt at a moving rate of 0.1-0.3 m / min and ultrasonically treating the melt, and obtaining the Ti-reinforced magnesium-based composite material after cooling.
4. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The protective atmosphere is a mixture of CO2 and SF6 in a volume ratio of (3-6):
1.
5. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The ultrasonic treatment time is 5 to 10 minutes.
6. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The ultrasonic treatment frequency is 50-100 Hz.
7. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The sintering time is 1.5~3h.
8. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The temperature of the magnesium-aluminum-zinc melt is 720-750°C.
9. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The titanium powder is powder treated by soaking in a citric acid solution.
10. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The particle size of the titanium powder is 400-600 μm.
11. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The titanium powder is an irregularly shaped powder.
12. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The pressure in the pressing step is 30-50T, and the pressing time is 3-10min.
13. The method for preparing the Ti-reinforced magnesium-based composite material according to claim 3, characterized in that: The preparation method of the magnesium-aluminum-zinc melt is as follows: heating the magnesium-aluminum-zinc raw materials to 680-700° C. and mixing them to remove impurities on the surface of the melt; then heating them to 720-750° C. and introducing a mixed gas of CO2 and SF6 in a volume ratio of (3-6):1 to obtain the magnesium-aluminum-zinc melt.
14. Use of the Ti-reinforced magnesium-based composite material according to any one of claims 1 to 2 or the Ti-reinforced magnesium-based composite material prepared by the preparation method according to any one of claims 3 to 13 in aerospace materials, engineering materials or building materials.
Citation Information
Patent Citations
Preparation method for titanium-magnesium double-metal composite of double-communication netted structure
CN106670464A